The Workability, Buildability and Compressive Strength of Printing Mortar Using Rice Husk Ash and Rubber Crumb - Abd Gafar, Nur Natasha; Abdullah, Siti Radziah (Recent Trends in Civil Engineering and Built Environment, 2025)
3D printing is computer-controlled to create three-dimensional shapes based on a digital model in the successive layering of materials. It is important that the fresh concrete used in 3D printing has good workability, buildability, and compressive strength to prevent the printable concrete layer from collapsing or deforming beyond acceptable limits. This objectives research was focusing on the interplay between workability, buildability, and compressive strength. incorporating with rice husk ash (RHA) and rubber crumb as sustainable replacements for cement and sand in printing mortar. Six mortar mixtures were investigated three control mixes with varying water-cement ratio (w/c) and superplasticizer content, and three replacement mixes incorporating 20% RHA and 10% rubber crumb alongside adjustments to maintain workability. From the study, it is found that slump tests revealed a strong negative correlation between w/c ratio and superplasticizer content with slump, confirming their influence on workability. Adding RHA and rubber decreased slump slightly for all replacement mixtures compared to their controls. The buildability of the concrete was measured by the yield stress measurements at 0, 10, 20, and 30 minutes after mixing, it showed expected increases over time due to hydration and setting. Control mixtures with lower w/c ratio and higher superplasticizer exhibited lower yield stress and improved flowability, suggesting better buildability. All replacement mixtures had higher yield stress than their controls at all time points. Compressive strength testing after 28 days of curing revealed that two replacement mixes achieved the acceptable Grade 35 standard. The mixture with the intermediate w/c ratio and higher superplasticizer content among the replacements displayed the highest compressive strength, highlighting the importance of optimizing mix design to compensate for the slight strength reduction due to RHA and rubber.